Comparison of the Effectiveness of Emotion Regulation Training Based on the Gross Model and Dialectical Behavior Therapy on Psychological Capital in Individuals with Visual Impairment - Masouminia, Sahar; Davari, Rahim; Tajail, Parisa (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to compare the effectiveness of emotion regulation training based on the Gross model and dialectical behavior therapy (DBT) on the psychological capital of individuals with visual impairment. Methods and Materials: This research employed a quasi-experimental method using a pre-test–post-test design with a control group and a follow-up phase. The statistical population included all individuals aged 17 to 30 years with visual impairments who were members of the Cultural and Welfare Services Association for the Visually Impaired in Tehran during the autumn and winter of 2024. A total of 60 participants were selected through convenience sampling and randomly assigned to two intervention groups—emotion regulation training based on the Gross model and dialectical behavior therapy—and one control group. Data collection was conducted using the Psychological Capital Questionnaire (McGee, 2011), and repeated measures ANOVA was applied for data analysis using SPSS version 25. Findings: The results indicated that the change in the optimism component during the post-test and follow-up stages was greater in the emotion regulation training group compared to the dialectical behavior therapy group. Conclusion: These findings suggest that while both therapeutic approaches had a significant impact on improving the psychological status of individuals with visual impairment, emotion regulation training was identified as a more effective intervention with a superior mechanism of action for enhancing psychological coherence.